The Unique Seed Protein Composition of Quality Protein Popcorn Promotes Growth of Beneficial Bacteria From the Human Gut Microbiome - Korth, Nate; Parsons, Leandra; Van Haute, Mallory J.; Yang, Qinnan; Hurst, Preston; Schnable, James C.; Holding, David R.; Benson, Andrew K. (Frontiers in Microbiology, 2022)
A growing about is known about the effects of fiber, complex carbohydrates, lipids, and small molecules from food matrices on the human gut microbiome. Much less is known about how dietary protein can influence the composition and function of the gut microbial community. Here, we used near-isogenic maize lines of conventional popcorn and Quality Protein Popcorn (QPP) to study the effects of the opaque-2 mutation and associated quality protein modifiers on the human gut microbiome. Opaque-2 blocks synthesis of the major maize seed proteins (α-zeins) and resulting in compensatory synthesis of new seed proteins that are nutritionally beneficial with substantially higher levels of the essential amino acids lysine and tryptophan. We show that QPP lines stimulate greater amounts of butyrate production by the microbiome using in vitro fermentation of popped and digested corn from parental and QPP hybrids with human microbiomes. In human gut microbiomes derived from diverse individuals, bacterial taxa belonging to the butyrate-producing family Lachnospiraceae, including the genera Coprococcus and Roseburia, were consistently increased when fermenting QPP vs parental popcorn lines. We used molecular complementation to further demonstrate that lysine-enriched seed protein can stimulate growth and butyrate production by microbes through distinct pathways. Our data shows that organisms such as Coprococcus can utilize lysine whereas other gut microbes such as Roseburia spp. instead utilize fructoselysine produced during thermal processing (popping) of the popcorn. Thus, the combination of seed composition in QPP and interaction of protein adducts with carbohydrates during thermal processing can stimulate growth of health-promoting, butyrate producing organisms in the human gut microbiome through multiple pathways.